An assessment of a mental imagery intervention for primary school children. - Howlett, Stephen G. (University of Ottawa (Canada), 1994)
An intervention designed to develop mental imagery skills was implemented in a primary school setting for children from grades 1 to 6. Children were separated into control and experimental groups and pre- and post-test measures were taken to determine the effects of the intervention on mental imagery ability. A self-report inventory, Kids Imagery Scale (KIS), and objective performance task, Ski Run Assessment Tool (Ski Run), were designed and administered to measure these effects. In addition, qualitative data collection was obtained from logging procedures during the intervention phase and questionnaires in post-test. Results showed significant improvement from experimental group children on the Ski Run scores but not on KIS scores. Qualitative analysis showed some indication of improved imagery ability of experimental group children. A secondary focus of the study examined the effects of the intervention on the mood and self-esteem of the children. The KISS Self-esteem Scale was designed and administered to measure change between groups and within groups. Though no significant improvement was realized, a significant correlation between self-esteem scores and KIS scores were found.
Keywords: Anthropology, Physical.